(untitled) (Central Medical College Journal, 2022)
Background: Orbit, having a volume of 30cc, contains neurosensory, vascular, motor and secretary structures; is surrounded by facial structures. Visual impairment and restricted ocular motility may be caused by diseases of these structures. Inflammation, neoplasia, structural abnormalities, vascular lesion, and degeneration and deposition can occur within or around the orbit. Objective: To evaluate the outcome of the management of vascular lesions of orbit and ocular adnexa attending at a tertiary eye hospital. Method: A prospective interventional study was conducted in a tertiary eye hospital, during the period of July, 2008 to June, 2010. A total of 60 patients with proptosis/lid growth irrespective of age and sex were selected for this study according to selection criteria. Method of medical and surgical treatment were recorded and postoperative details examination including visual acuity, amount of proptosis, cosmetic outcome had been done. Patients were followed after first day, first week, six weeks and six months of postoperative period. Result: In vascular lesion of the orbit, 53.33 % patients were cavernous haemangioma, 26.67 % patients were capillary haemangioma, 8.33%patients were orbital varices, 6.67 % patients were lymphangioma and 5 % were haemangiopericytoma. Only 10 (16.67%) cases managed by medical treatment and bulk of the patients about 50 (83.33%) patients surgically managed. 10 (62.5%) patients of capillary haemangioma were managed by medically. Among the surgical complications stitch granuloma was higher (10) followed by recurrence (6). There were no complications occurred in 30 (50%) cases. Conclusion: Cavernous haemangioma was higher among vascular lesions of orbit and adnexa treated surgically. Central Medical College Journal Vol 5 No 1 Jan 2021 PP 20-24